A window-space-directed assembly strategy for the construction of supertetrahedron-based zeolitic mesoporous metal–organic frameworks with ultramicroporous apertures for selective gas adsorption. Issue 16 (10th March 2021) - Zhang, Lei; Li, Fangfang; You, Jianjun; Hua, Nengbin; Wang, Qianting; Si, Junhui; Chen, Wenzhe; Wang, Wenjing; Wu, Xiaoyuan; Yang, Wenbin; Yuan, Daqiang; Lu, Canzhong; et al.
Abstract : A series of supertetrahedron (ST)-based sodalite (sod )-topology zeolitic MOFs specimens ST-sod -MOFs featuring ultramicroporous square windows and a mesoporous sodcage have been synthesized via a window-space-directed assembly approach. Abstract : Despite their scarcity due to synthetic challenges, supertetrahedron-based metal–organic frameworks (MOFs) possess intriguing architectures, diverse functionalities, and superb properties that make them in-demand materials. Employing a new window-space-directed assembly strategy, a family of mesoporous zeolitic MOFs have been constructed herein from corner-shared supertetrahedra based on homometallic or heterometallic trimers [M3 (OH/O)(COO)6 ] (M3 = Co3, Ni3 or Co2 Ti). These MOFs consisted of close-packed truncated octahedral cages possessing a sodalite topology and large β-cavity mesoporous cages (∼22 Å diameter) connected by ultramicroporous apertures (∼5.6 Å diameter). Notably, the supertetrahedron-based sodalite topology MOF combined with the Co2 Ti trimer exhibited high thermal and chemical stability as well as the ability to efficiently separate acetylene (C2 H2 ) from carbon dioxide (CO2 ).